An effective strategy for removing tetracycline from water: Enhanced adsorption reliability and capacity by tyrosine modified layered hydroxides. Issue 1 (February 2023) - Xia, Caifeng; Li, Xiangming; Xie, Yuan; Kong, Fanping; Zhao, Menglan; Wang, Yu; Wang, Yang; Zhang, Qian; Meng, Zilin
Abstract: The discharge of tetracycline (TCs) antibiotics into the natural environment poses a serious threat to human beings. In the removal of antibiotics by adsorption method, both increase of adsorption capacity and enhancement of adsorption reliability should be considered. In this study, tyrosine intercalated layered double hydroxide (Tyr@LDH) was prepared by a one-step method and characterized by XRD, FT-IR, and SEM. Adsorption kinetics and isotherms studies revealed that compared with LDHs, the adsorption of TC by Tyr@LDH was a multi-layer adsorption process, with more adsorption sites and larger adsorption capacity. Thermodynamic experiments showed that increasing temperature was beneficial to TC adsorption, indicating adsorption was an endothermic process. In the results of the molecular dynamics study, TC molecules entered the interlayer of LDHs by hydrophobic interaction, and possessed strong interactions with Tyr molecules by electron donor and acceptor, hydrogen bonding, and electrostatic interaction. The antibacterial experiments showed that the inhibition zone of Tyr@LDH was smaller than that of LDHs, indicating that with the presence of Tyr, TC molecules were adsorbed reliably. pH, coexisting ions, and recycle experiments proved that 1-Tyr@LDH had reliable adsorption for TC and stability in complex environments. Overall, Tyr@LDH material was expected to be an adsorbent with good adsorption efficiency and reliable adsorption performance for the treatment of TC from the environment. Graphical Abstract: ga1 Highlights: Tyr@LDH improves TC adsorption capacity by creating more adsorption sites. Molecular dynamic simulation is selected to explore adsorption process of TC. Multiple interactions between Tyr and TC lead to stable adsorption of Tyr@LDH. Antibacterial experiments verify the reliability of TC adsorbed by Tyr@LDH.